TRAINING AND MENTORING SKILLS FOR WRITING SCIENTIFIC ARTICLES FOR UNIVERSITY STUDENTS: EFFORTS TO INCREASE STUDY PROGRAM ACCREDITATION SCORES - Zahara Adibah, Ida; Khasanah, Uswatun; Stiyaningrum , Puput; Sofiyah, Siti (Tahta Media Grup, 2024)
The low quality of university students' scientific article writing and the demand for article writing as a separate point in the accreditation score demands the best solution to overcome this problem. So it is necessary to carry out a service that aims to improve the students' article writing skills through training and mentoring. This community service program is carried out to improve the ability of students of the Faculty of Islamic Education (FAI) Undergraduate Program in Islamic Education at Darul Ulum Islamic Center Sudirman University, Semarang Regency to write and publish scientific articles. The number of participants in this community service program is 25. The form of community service activities is training and mentoring with the following training methods: 1) Lecture method; 2) Question and answer method; and 3) Assignment/Simulation method. The results of this mentoring are that the training participants are enthusiastic about the training material provided. This can be seen from the beginning to the end of the event, all participants followed it well. Based on the evaluation results, it can be identified that the level of understanding of the community service participants is that 84% of the participants understand the skills of writing scientific articles for students.